If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 2 = CBD Reorder the terms: 2 + 6x = CBD Solving 2 + 6x = BCD Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 6x = -2 + BCD Combine like terms: 2 + -2 = 0 0 + 6x = -2 + BCD 6x = -2 + BCD Divide each side by '6'. x = -0.3333333333 + 0.1666666667BCD Simplifying x = -0.3333333333 + 0.1666666667BCD
| (20x^-3)/(2x^-5) | | log[3](x-5)+log[3](x+3)=2 | | 1/2(ln2-ln1) | | 77/s=132/48 | | -x^2+x-18= | | X/4=80 | | 0.7x=0.864 | | -4(4y-5)+3(3y+5)= | | 8/t=840/210 | | 9p=96 | | 2x^2-3x+.05=0 | | e^4=y | | 250y-y^2=10000 | | A/5=105 | | y/493=228/116 | | 664/996=r/12 | | N/2=33 | | 15n-125=175 | | 4x-3y/8z | | 1=3-d | | 28/42=y/12 | | 12/14=t/42 | | X/8=-1 | | X=16.50-(3.25+1.75) | | 3x^2-6x+4x+4=3x^2-3x-6 | | 3n+n=165 | | x/87/2 | | 12/15=y/35 | | Y/8==-96 | | 6(11x-10)/512 | | x+7.1=10.6 | | 10=32t-5t^2 |